Carbapenem resistance exposures via wastewaters across New Delhi. (October 2018) - Lamba, Manisha; Gupta, Sonia; Shukla, Rishabh; Graham, David W.; Sreekrishnan, T.R.; Ahammad, S.Z.
Abstract: Antimicrobial resistance (AMR) is a major global concern, especially in India where the burden of infectious diseases is high and health care spending is low. Here we quantified total coliform, faecal coliforms (FC), carbapenem-resistant enteric bacteria (CRE), bla NDM - 1, and three integron genes in samples collected from wastewater effluent of 12 hospitals, 12 sewage treatment plants (STPs), 20 sewer drains, and five locations along the Yamuna River in New Delhi over two seasons. Significant correlations were found between FC levels, CRE ( r  = 0.903, p  = 0.004, n  = 49) and bla NDM-1 ( r  = 0.787, p  = 0.003, n  = 49) concentrations across all samples. Concentrations of coliforms, CRE, bla NDM-1, int1, and int3 were highest in hospital effluents compared to other locations in both seasons. Although absolute concentration data indicate greater abundances of CRE and bla NDM-1 in the winter, normalised data indicates greater carriage of bla NDM-1 per cell in summer samples. In general, observed CRE levels were highest in surface water downstream of areas with higher population densities. Among CRE isolates ( n  = 4077), 82%, 75%, 71% and 43% of the strains from hospitals, sewer drains, river samples, and STPs, respectively, contained bla NDM-1, implying STPs have relatively fewer bla NDM-1 positive CRE in their effluents. The most common CRE isolates in the drains were Pseudomonas putida (39%) followed by Acinetobacter baumanni (20%) and Pseudomonas montelli (19%). The present scenario in New Delhi highlights the urgent need for increased coverage of appropriate waste treatment facilities across the city to reduce CRE exposures from polluted surface waters. Graphical abstract: Seasonal CRE exposures in New Delhi surface waters. Highlights: High levels of carbapenem-resistant enteric bacteria (CRE) in New Delhi surface water Significant correlations among CRE, bla NDM-1, and faecal coliform levels were observed. Highest levels of CRE and bla NDM-1 were observed in hospital samples. Poor linkages between drains and STPs have elevated AMR levels in the river. CRE obtained from samples were dominated by pathogens on the WHO critical list.